Post-Fracture Stiffness and Residual Capacity Assessment of Film-Retrofitted Monolithic Glass Elements by Frequency Change - Bedon, Chiara; Fasan, Marco (Mathematical Problems in Engineering, 2024)
The primary goal of safety films for glass in buildings is to retrofit existing monolithic elements and prevent, in the post-fracture stage, any fall-out of shards. Their added value is that—as far as the fragments are kept bonded—a cracked film-glass element can ensure a minimum residual mechanical and load-bearing capacity, which is strictly related to the shards interlocking and debond. To prevent critical issues, such a mechanical characterization is both important and uncertain, and requires specific methodologies. In this regard, a dynamic investigation is carried out on fractured film-bonded glass samples, to assess their post-fracture stiffness trends and its sensitivity to repeated vibrations. The adopted laboratory layout is chosen to assess the effects of random vibrations (220 repetitions) on a total of 12 cracked specimens in a cantilever setup (with 0.5–5 m/s2 the range of randomly imposed acceleration peaks). By monitoring the cracked vibration frequency, the film efficiency and corresponding residual bending stiffness of cracked glass samples are quantified as a function of damage severity, with a focus on fragments interlock. Quantitative experimental estimates are comparatively analyzed and validated with the support of finite element (FE) numerical models and analytical calculations. As shown—at least at the small-scale level—a progressive post-fracture stiffness reduction takes place under repeated random vibrations, and this implicitly affects the residual load-bearing capacity of glass members. Most importantly, for the tested configurations, it is shown that the cracked vibration frequency is minimally affected by crack geometry, and follows a rather linear decrease with the number of imposed random impacts (up to an average of ≈20 for each sample), thus confirming the retrofit potential and efficiency in providing some mechanical capacity through fragments interlock.